A bioinspired and biocompatible ortho-sulfiliminyl phenol synthesis - Feng Xiong (Nature Portfolio, 2017)
Functionalization of C-H bonds typically requires harsh reagents or metal catalysts. Here the authors report a metal-free C-H sulfenylation/rearrangement to form C-S and S=N bonds under simple, biocompatible conditions, and apply this to the synthesis of fluorogenic phospholipid vesicles.